ADDRESSING THE NEGLECT OF HIGH SCHOOL STUDENTS TOWARDS TEACHER’S LESSONS: STRATEGIES FOR ENGAGEMENT AND EMPOWERMENT - Fayzullayeva , Mashhura Habibullo qizi; Yugay , Yevgeniya (Innovative Development in Educational Activities, 2023)
This thesis aims to explore and propose practical strategies to counteract the issue of neglect displayed by high school students towards their teachers’ lessons and it investigates the underlying causes of neglect and presents a range of proactive measures that can be implemented to foster students’ engagement, motivation, and respect towards their teachers and lessons.